Evaluation of the effect of endometrial scratch by hysteroscopic scissors on frozen embryo transfer outcomes: A historical cohort study - Sara Saedi; Amirhossein Tayebi; Maedeh Ghorbani Kahrizsangi; Fatemeh Jalalinezhad; Aryan Ayati; Alireza Hadizadeh; Bita Badehnoosh; Atousa Karimi (Shahid Sadoughi University of Medical Sciences, 2023)
Background: Endometrial scratch (ES) has been suggested to improve assisted reproductive techniques success rates by investigating implantation failure. Objective: In this study, we evaluated the effect of ES on the outcomes of frozen embryo transfer (FET) in women with at least 2 failed embryo transfer cycles. Materials and Methods: In this historical cohort study, medical data of 236 infertile women who underwent in-vitro fertilization-FET at Ebne-sina Infertility Center, Tehran, Iran, from January 2015-December 2021 was extracted from their medical records. Based on having ES before FET, they were assigned to either the scratch (n = 118) or the no-scratch group (n = 118). We compared these groups regarding pregnancy rates and outcomes. Results: The demographic characteristics were similar in both groups regarding weight, body mass index, the number of previous embryo transfers, and the duration of infertility. However, the scratch group had a slightly higher mean age (32.31 vs. 29.96 yr, p < 0.001). No statistically significant difference was observed between groups regarding pregnancy rate (p = 0.89). No significant association was observed between scratch, infertility duration, the number of previous FET attempts, and the likelihood of pregnancy in a logistic regression model. No major complications were observed. Conclusion: Hysteroscopic endometrial scratching with scissors probably has no effect on FET outcomes, including pregnancy or live birth rates.